Government debt as the integral portfolio of assets and liabilities generated by debt - Rutkauskas, Aleksandras Vytautas; Stasytytė, Viktorija; Maknickienė, Nijolė (Journal of Business Economics and Management, 2014)
The paper analyses the possibilities of optimal government (national) debt management, trying to maximize the made-up net value for the debtor with the help of funds borrowed by the government. The integral portfolio of debtor assets and debt service liabilities, based on the borrowed funds, is chosen as a solution for the above-described problem. In the paper, an asset is understood as a position of government expenditures, where funds borrowed by the government are used and create a quantifiable profit (value) or the measurable damage or loss is avoided if funds are borrowed. Actually, liabilities are the main debt service positions. Naturally, the value generated by assets, as well as funds spent to settle the liabilities, could be analytically adequately evaluated only in stochastic dimension. Consequently, multidimensional multicriteria stochastic optimization technique is used as a technical solution to the formulated problem. In analytical decisions, the budget funds borrowed by the government are treated as marginal funds. Taking into account a completely new decision technique that has been invoked for government debt management, the methods of decisions are described quite particularly. First published online: 02 Oct 2013